2020
DOI: 10.1002/ejhf.1796
|View full text |Cite
|
Sign up to set email alerts
|

Association between loop diuretic dose changes and outcomes in chronic heart failure: observations from the ESC‐EORP Heart Failure Long‐Term Registry

Abstract: Guidelines recommend down-titration of loop diuretics (LD) once euvolaemia is achieved. In outpatients with heart failure (HF), we investigated LD dose changes in daily cardiology practice, agreement with guideline recommendations, predictors of successful LD down-titration and association between dose changes and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 44 publications
2
48
1
Order By: Relevance
“…heart failure therapy, hemodynamic stress (NT‐proBNP) and decongestion (haemoconcentration)] to be similar in both AKI groups, which appears to support our conclusions. Furthermore, the degree of persistent acute renal dysfunction and the need for chronic diuretic therapy at discharge were significantly lower in patients initially presenting with CA‐AKI 12 …”
Section: Limitationsmentioning
confidence: 97%
“…heart failure therapy, hemodynamic stress (NT‐proBNP) and decongestion (haemoconcentration)] to be similar in both AKI groups, which appears to support our conclusions. Furthermore, the degree of persistent acute renal dysfunction and the need for chronic diuretic therapy at discharge were significantly lower in patients initially presenting with CA‐AKI 12 …”
Section: Limitationsmentioning
confidence: 97%
“…Data from the ESC‐HFA EORP HF Long‐Term Registry showed that diuretic dose increase (vs. no change) was associated with HF death, while a decrease had a trend for better outcomes. Predictors of successful down‐titration of loop diuretics were higher systolic blood pressure, the absence of sleep apnoea, peripheral congestion and significant mitral regurgitation 17 …”
Section: Medical Treatmentmentioning
confidence: 99%
“…2 Given the low rate of LD adjustments, it may be speculated that clinical assessment was not sufficiently extensive, at least in some patients. 1 In contrast to down-titration, up-titration was related to worse outcome. The authors noted that extensive adjustment was done to prove the independence of up-titration as a risk factor.…”
mentioning
confidence: 99%
“…We read with interest the recent investigation by Kapelios et al 1 concerning the analysis of the European Society of Cardiology Heart Failure Long-Term (ESC-HF-LT) registry. It underscores the widespread inertia in congestion management, as only 24% of patients underwent loop diuretic (LD) dose modification in ESC-HF-LT registry.…”
mentioning
confidence: 99%
See 1 more Smart Citation